Association between Head-to-Chest Circumference Ratio and Intrauterine Growth-Retardation Related Outcomes during Preweaning and Postweaning - Diego Manriquez; Guilhem Poudevigne; Etienne Roche; Agnes Waret-Szkuta (Animals, 2022)
The objective of this study is to evaluate the association between the head-to-chest circumference ratio (HCR) and birth weight (BW), colostrum intake, and average daily weight gain (ADG) at preweaning and postweaning periods. Additionally, associations between HCR and PCV-2 serum antibody titers and the PCV-2 seroconversion ratio (SCR) were assessed. Head and chest circumferences were measured at birth, and HCR was calculated from 110 piglets born from 8 pregnant sows randomly selected from maternity pens. Linear mixed models were used to test whether changes in HCR were associated with fluctuations of BW, colostrum intake, and ADG. In addition, HCR least-square means were compared between piglets classified as lower or greater BW, colostrum intake, and ADG. Finally, receiving operating characteristic curve analyses were performed to estimate HCR thresholds for discriminating between lower and greater performance piglets during preweaning and postweaning periods. Increments in HCR were associated with lower BW, colostrum intake, and ADG. An HCR threshold of 0.82 maximized sensibility and specificity for the classification of lower and greater performance piglets regarding BW, colostrum intake, and ADG during the periods of 0 to 7 and 0 to 69 days of life. When piglets were categorized into HCR ≤ 0.82 and HCR > 0.82 groups, piglets with HCR ≤ 0.82 had lower (log10) PCV-2 serum antibody titers at 26 days of life compared with piglets with HCR > 0.82 (3.30 ± 0.05 vs. 3.47 ± 0.05 g/dL). On the other hand, piglets that showed low SCR between 26 and 69 days of life had greater HCRs compared with piglets with high SCRs (0.83 ± 0.008 vs. 0.8 ± 0.008). The use of HCRs allowed us to identify piglets with lower performance and impaired immune response against PCV-2. The HCR indicator could be used as a selection criterion for preventive management for piglets showing delayed performance potentially associated with IUGR.